1557 Alterations in cerebral blood flow during the postdrome phase of a migraine attack captured with arterial spin labelled (asl) mri. (1st December 2017) - Bose, Pyari; Karsan, Nazia; Zelaya, Fernando; Goadsby, Peter
Abstract : Background: Symptoms patients experience in the premonitory and postdromal phase of migraine are broadly similar. The postdrome of a migraine attack, however, is poorly characterised and largely unexplored in literature. No functional imaging study has evaluated the postdrome phase in depth. Aim: To study the alterations in cerebral blood flow during the postdrome phase of a migraine attack using arterial spin labelled (ASL) MRI in nitroglycerin-induced migraine attacks. Method: Sixteen subjects completed three study visits in the study. ASL MRI scans over the course of triggered migraine attacks were analysed (SPM 12, www.fil.ion.ac.uk/spm). Results: Significant alterations were detected in rCBF over the superior frontal gyrus, medial frontal gyrus, middle frontal gyrus, putamen, superior temporal gyrus, middle temporal gyrus, inferior temporal gyrus, thalamus, hypothalamus, midbrain, posterior cingulate, anterior cingulate, claustrum (p<0.001) in the postdrome phase compared to premonitory phase Conclusion: The brain processes involved in the premonitory phase and postdrome phase are different. The symptoms experienced by subjects in the postdrome are associated with a near global reduction in cerebral blood flow.